Factors influencing financial inclusion among university students in Malaysia: an empirical research for International Islamic University Malaysia (IIUM) - Abdul Razak, Dzuljastri; Abdisalan Nor, Bile; Mohamed Noor, Siti Fatimah; Amin, Hanudin (Zes Rokman Resources, 2023)
The issue of financial inclusion affecting students are very important as it may cause financial distress to themselves which will have high impact on their daily life. This will also have high consequences on the performances of their studies. The purpose of this study is to examine the relationship of three variables namely financial attitude, financial behaviour and financial literacy on financial inclusion. A survey of 277 students from International Islamic University Malaysia (IIUM) were carried out using on line survey and face to face methods. Data analysis were processed using SPSS. The correlation results indicated that financial attitude, financial behaviour and financial literacy significantly explained financial inclusion. Besides, the R2 also presented that all three variables described the financial inclusion among the university students by 62 %. The regression results indicated that financial attitude and financial literacy are significant predicators of financial inclusion. However, financial behaviour is not significant. The lack of significance between financial behaviour and financial inclusion warrants further exploration. It may indicate that actual financial practices among students may not be all directly influencing their level of financial inclusion. This could be attributed to external factors, such as economic conditions, institutional support or cultural influences that impact financial behaviours beyond individual attitudes and literacy. Hence, the regulators can focus on improving students mind set and attitude. As for financial literacy and skills more knowledge and training should be organized for them to improve financial inclusion. Further research could delve into the specific determinants of financial behaviour and explore additional variables contributing to financial inclusion among this demographic.